Examining natural resource management through a community development theoretical lens. Issue 2 (15th March 2022) - Oliver, Matt D.; Stout, Margaret
ABSTRACT: The United States Department of Agriculture (USDA) Natural Resources Conservation Service (NRCS) is a government agency that seeks to integrate conservation goals with farmers' economic goals through voluntary private efforts, particularly through its Conservation Technical Assistance (CTA) program. Researchers note a lack of theoretical grounding in the associated body of literature. Therefore, a comprehensive theory of change was developed to guide a study of farmer adoption of conservation practices. The theoretical model incorporates factors from the Asset-Based Community Development (ABCD) approach and Community Capitals Framework (CCF). The purpose of this paper is to explain this theoretical model and discuss how it better conceptualized and operationalized variables that influence farmer conservation practice adoption. Because later empirical findings largely supported the anticipated causal hypotheses, the use of community development theory to understand other public programs that seek to achieve policy goals through voluntary, co-productive change on the part of participants is reasonable.